Existence of Nonoscillatory Solutions for System of Higher-Order Neutral Differential Equations with Distributed Deviating Arguments - Youjun Liu; Jianwen Zhang; Jurang Yan (Discrete Dynamics in Nature and Society)
In this paper, we consider the existence of nonoscillatory solutions for system of variable coefficients higher-order neutral differential equations with distributed deviating arguments. We use the Banach contraction principle to obtain new sufficient conditions for the existence of nonoscillatory solutions.